The Role of Government Regulation in Increasing Human Resource Productivity in the Gig Economy Sector - Panjaitan, Maludin; Panjaitan, Yosie Gabriela; Permana, Yosua; Grace, Yosephine; Jamaludin, Maun (JURNAL AKTA, 2024)
The gig economy has witnessed rapid growth in recent years, transforming the nature of work and labor markets globally. This paper examines the relationship between government regulation and human resource productivity within the gig economy. It explores the challenges faced by gig workers, including job security, income uncertainty, and the lack of labor protections. The role of government regulation in addressing these challenges and boosting human resource productivity is discussed, with a focus on fair pay, benefits, workplace safety, anti-discrimination laws, and training initiatives. The paper also reviews how productivity is influenced by flexibility and autonomy, and how well-being impacts worker output. Ultimately, the paper argues that well-crafted regulations are essential for enhancing productivity while ensuring fair treatment and opportunities for gig workers.